2023
DOI: 10.1590/1807-1929/agriambi.v27n5p352-358
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiology of ‘Sunrise’ papaya seedlings in response to salinity and humic acid

Abstract: Salinity is one of the major obstacles to agriculture in semi-arid regions, as it affects the physiological processes, growth, and yield of numerous crops. Hence, the application of salt stress attenuators is of paramount importance, as it enables the use of saline water for agricultural purposes. Among these, humic acid promotes the growth as well as water and nutrient uptake of plants. To this end, the present study evaluated the effects of humic acid on the growth and physiology of Carica papaya seedlings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Humic substances (HS) have been used to supply nutrients and/ or stimulate the production of phytohormones that lead to root growth that the plant would otherwise not achieve (El-Hai et al, 2019;Qin & Leskovar, 2020a;Soteriou et al, 2021). Previous studies have demonstrated the effect of humic substances as seedling growth modulators, among other beneficial effects (Gomes Júnior et al, 2019;Qin & Leskovar, 2020a;Silva et al, 2022;Targino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Humic substances (HS) have been used to supply nutrients and/ or stimulate the production of phytohormones that lead to root growth that the plant would otherwise not achieve (El-Hai et al, 2019;Qin & Leskovar, 2020a;Soteriou et al, 2021). Previous studies have demonstrated the effect of humic substances as seedling growth modulators, among other beneficial effects (Gomes Júnior et al, 2019;Qin & Leskovar, 2020a;Silva et al, 2022;Targino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%